The Relationship Between University Research And The Marketability Of Universities - Simona Vasilache; Alina Mihaela Dima; Mihaela Dan (Amfiteatru Economic Journal, 2011)
As universities are presently involved in a world-wide competition for students, and, implicitly, for markets in which to sell their services, the issue of the advantages research brings, transformed in market share increase, becomes an issue for university management. The paper examines, comparatively, the profitability of basic and applied research in terms of strengthening the market position of a university actively involved in one type of research or in both at a time. Well developed indicators to measure the relationship between research activity and prestige, on the one hand, social capital, on the other, and we will correlate these two research outcomes with the university market share and competitive advantage. The interest a university has to invest in its research activities has a market feedback, which provides a sense of involvement for practical reasons, and that goes beyond the bare purpose of reporting results .
Keywords: I23; C22; M14; 330; entrepreneurial university; performance ratios; basic and applied research